The World's Parliament of Religions : the East/West encounter, Chicago, 1893 - Seager, Richard Hughes (Religion in North America., 1995)
The 1893 World's Parliament of Religions was much more than a religious assembly. It was conceived as a presentation of the major religious forces at work in the late nineteenth century. The goal of the Parliament was "to unite all religion against irreligion," and many observers celebrated that spirit. Some saw the Parliament as a sign of the coming fulfillment of missionaries' hope to evangelize the world, but others saw it as a disaster for missionaries. Some thought it proved the superiority of Christianity; others saw a victory for the religions of the East. Some thought the Parliament pointed toward the coming unity of all Christians, while for others it seemed a revelation of the forces dividing Christendom. Seager's beautifully fashioned narrative explores this fascinating event in all its complexities and establishes it as truly a watershed event in the emergence of a more pluralistic religious culture in America.